Positions of Dual-band Textile Diamond Dipole Antenna with Dual-band Textile Artificial Magnetic Conductor Waveguide Sheet for Body Centric Communication - Abdullah, M. A; A.Rahim, M.K.; Samsuri, N.A. (ELEKTRIKA- Journal of Electrical Engineering, 2017)
A dual-band textile Artificial Magnetic Conductor (AMC) sheet-like waveguide with dual-band textile diamond dipole antennas were designed for enhancing the transmission between the two antennas. The AMC surface is designed to have in-phase reflection at 2.45GHz and 5.8GHz with the objective to enhance the transmission between antennas. Both structures were made of fleece fabric with conductive patches made of SHIELDIT fabric. The performance of the two antennas with textile AMC sheet was investigated thoroughly in terms of transmission coefficient (S21) parameters. The effect of different antennas’ placement was also considered. Measurements were conducted rigorously to validate the simulated findings. Results showed that the S21 transmission between antennas improved significantly when incorporated with AMC waveguide sheet.